Survey sarana dan prasarana pembelajaran softball di SMA Se- Kabupaten Jepara - Sirojul Habib; Osa Maliki; Donny Anhar (YLPK Mahardhika, 2021)
Purpose of this study to determine how the facilities and infrastructure for softball learning in Senior High School Jepara Regency. This research uses qualitative research with a descriptive approach, with the subject of this research is the Senior High School teachers in Jepara district. The collecting data using interview, observation and documentation methods. The data analysis using methods that are carried out continuously with data reduction, data presentation and make a conclusions. The results showed that (1) From 9 State Senior High Schools in Jepara Regency had good softball facilities and infrastructure, because there were several schools that did not have the facilities. (2) The main inhibiting factor in the procurement of softball facilities is the price of equipment which is expensive and in large quantities. (3) Softball learning in the school has not run optimally, due to inadequate facilities and infrastructure. (4) The teacher is innovative enough in learning to modify the tools and how to play. The conclusion is that the price of softball equipment is very expensive and the amount of equipment is not small, so the implementation of softball learning in the schools has not been carried out properly, because of the lack of softball equipment and also requires a large field. It is hoped that schools whose facilities and infrastructure for softball learning are still inadequate should be available to immediately organize softball facilities and infrastructure while still considering the level of need, so the quality of learning outcomes for sports and health, softball material can run well and can also lift branches Softball in Jepara Regency has become a popular sport not only among students but also among the local community.